Periodontal Health And Microbiological Characteristics Of Siwak (chewing Stick) And Toothbrush Users: A Cross-sectional Study - Winarni Yasmin; Rathna Devi Vaithilingam; Nadia Halib; Rohazila Mohamad Hanafiah; Haslinda Ramli (Thieme, 2024)
Indexed by Scopus